Religion and Social Change: Some Basic Patterns - Chethimattam, John B (Journal of Dharma, 1984)
Organized religion has often a predilection for the status quo and stands in the way of a healthy transformation of outmoded social structures. On the other hand, réligion provides the most potent motivation for transforming society in accordance with the principles and ideals that define the ultimate concerns of man as a social being. But this religious orientation towards social change has assumed different approaches. Here I shall present a few basic patterns of the relationship of religion to social structures, their preservation, development and transformation.